Early effectiveness and safety analysis of belimumab in addition to standard treatment in patients with systemic lupus erythematosus - Lingyan He; Mingming Yan; Rui Wen; Jiali Li (Archives of Rheumatology, 2024)
Objectives: This study aimed to evaluate the early effectiveness and safety of belimumab in addition to standard therapy in patients with systemic lupus erythematosus (SLE) for 24 weeks. Patients and methods: This retrospective study was conducted with 60 adult patients with active SLE between June 2020 and August 2022. The patients either received intravenous belimumab in addition to standard therapy (n=31; 24 females, 7 males; mean age: 33.7±14.1 years; range, 18 to 52 years) or only standard therapy (n=29; 22 females, 7 males; mean age: 34.1±13.4 years; range, 19 to 66 years) for 24 weeks. Outcome measures, including safety and effectiveness (Safety of Estrogens in Lupus Erythematosus National Assessment–Systemic Lupus Erythematosus Disease Activity Index [SELENA-SLEDAI]), changes in biomarkers (double-stranded DNA [deoxyribonucleic acid]), serum complement levels, and immunoglobin G (IgG) were recorded. Adverse events were recorded. Results: Baseline demographic and clinical characteristics were similar between the two groups. More patients in the belimumab group achieved a reduction of ≥4 points in SELENA-SLEDAI at weeks 12 and 24 (week 12, 77.4% vs. 41.4%, p=0.008; week 24, 87.1% vs. 48.3%, p=0.002). The mean score of SELENA-SLEDAI was significantly lower in the belimumab group compared to the standard therapy group at week 12. However, a significant difference was not reached at week 24. Moreover, mean levels of serum C3 and C4 in the belimumab group were significantly higher than those in the standard therapy group at weeks 12 and 24. A higher proportion of patients in the belimumab group had a normal C3 level than in the standard therapy group. In addition, belimumab treatment resulted in a significant decrease in IgG levels at both weeks 12 and 24. At week 24, the belimumab group had a higher reduction in prednisone dose than the standard therapy group. Furthermore, the percentages of patients with more than 50% reduction in prednisone over baseline were significantly greater for belimumab versus standard therapy at week 12 (p=0.002). The occurrence of adverse events was similar between the two groups (standard therapy group, 44.8%; belimumab group, 51.6%). Conclusion: Intravenous belimumab was well tolerated and significantly improved disease activity in Chinese patients with SLE at the early stage of treatment. More importantly, belimumab treatment could result in a rapid reduction in prednisone dose as early as week 12.